PENDAMPINGAN PENGEMBANGAN UNIT USAHA MAKANAN DI RESTO PESANTREN DARUN NASYA DENGAN MENGGUNAKAN ANALISIS SWOT - Raeni Dwi Santy (ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Developing a business unit requires a strategic business to ease decision-making by considering many factors, both internal and external. The party who is a partner in the implementation of this Community Service is the Resto Pesantren Darun Nasya which is a business unit of the Darun Nasya Islamic Boarding School. The business unit is located in Desa Pagerwangi, Kec. Lembang, Kab. Bandung Barat. The purpose this Community Service is to find out the existing conditions and provide recommendations regarding the development of the business unit. The method used is SWOT analysis. The result of the analysis is to focus on the strength-opportunity (SO) strategy or on the aggressive quadrant which is implemented by obtaining capital injections and adding new online marketing channels.